Media Lectora Inspire Dalam Pembelajaran Pendidikan Agama Islam Di SMP- Negeri 3 Colomadu Tahun Pelajaran 2015/2016 - Permatasari, Siska Bungkus, Dr. Mohamad Ali, S.Ag, M.Pd (2016)
Lectora Inspirea is a computer program that is functioning in developing electronic learning tool. In developing student's interest of Islamic study it needs a school which can contibute maximally in increasing student's interest. Based on the background of study above can be formulated the problem statement about how the implementation of Islamic Education which uses Lectora Inspirea media on VIII grade student of SMP N 3 Colomadu in 2015/2016 academic year and what are the support and obstacle factors of implementation of Islamic Education which uses Lectora Inspirea media on VIII grade student of SMP N 3 Colomadu in 2015/2016. The objectives of this research is to describe the implementation of Islamic Education which uses of Lectora Inspirea media on VIII grade student of SMP N 3 Colomadu in 2015/2016 and to describe the support and obstacle factors of implementation Islamic Education which uses Lectora Inspirea media on VIII grade student of SMP N 3 Colomadu in 2015/2016. The type of research is a field research. The methods of collecting data are documentation, observation, and interview. While analysing of result in this research uses of deductive analysis which stand from five activities, there are collecting data and analysing the whole data of various sources (interview, observation, and documentation), reducing the data, then filtering data based on the theory and problem statement, the data is presented in narative, and concluding the summary. The research shows that the priority of Lectora Inspirea media on VIII grade student of SMP N 3 Colomadu in 2015/2016 is to increase the student interest. The increase of student's interest will increase the grade of achievement of student in Islamic education. Keywords: Media, Lectora Inspirea, Islamic Education